1998
DOI: 10.1073/pnas.95.12.6797
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic lengths of neutrophil microvilli

Abstract: Containing most of the L-selectin and Pselectin glycoprotein ligand-1 (PSGL-1) on their tips, microvilli are believed to promote the initial arrest of neutrophils on endothelium. At the rolling stage following arrest, the lifetimes of the involved molecular bonds depend on the pulling force imposed by the shear stress of blood f low. With two different methods, electron microscopy and micropipette manipulation, we have obtained two comparable neutrophil microvillus lengths, both Ϸ0.3 m in average. We have foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
341
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(386 citation statements)
references
References 31 publications
40
341
5
Order By: Relevance
“…Alternatively, the excess membrane may not form a flat contact area, but rather be withdrawn as a single tether anchored at the capture site. This mechanism has been hypothesized to stabilize leukocyte adhesion by transferring energy from breaking of the tethering bond to extending the microvilli [28,29]. Our observations of elongated microbubbles do not seem to support the possibility of tethers.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Alternatively, the excess membrane may not form a flat contact area, but rather be withdrawn as a single tether anchored at the capture site. This mechanism has been hypothesized to stabilize leukocyte adhesion by transferring energy from breaking of the tethering bond to extending the microvilli [28,29]. Our observations of elongated microbubbles do not seem to support the possibility of tethers.…”
Section: Discussioncontrasting
confidence: 80%
“…Additionally, binding through outward-projected microvilli may stabilize adhesion by altering the fluid force distribution upon the adhesive bonds. For example, projection of the adhesive ligand away from the body of the cell decreases the force on the rearmost load-bearing bond [26,27], and tethering through extensible microvilli may further decrease the stress on the bond between the targeting ligand and receptor [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments and numerical simulations demonstrate that formation of membrane tethers reduces the force exerted on specific bonds (i.e. selectin-PSGL1) and increases bond lifetime, which results in increased chance of adherence of neutrophils to the endothelium (Girdhar and Shao, 2004;Ramachandran et al, 2004;Schmidtke and Diamond, 2000;Shao, 1998). Our model calculation illustrates that after cholesterol enrichment, the force exerted on the specific bond formed between an endothelial tether and a leukocyte decreases much faster than in the control or depleted cases (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Earlier work has confirmed that tether formation can reduce the force exerted on the specific bonds (the bond force, F b ) between endothelial cells of the vascular wall and leukocytes, and thus result in increased chance of adherence between the two cell types (Girdhar and Shao, 2004;Ramachandran et al, 2004;Schmidtke and Diamond, 2000;Shao et al, 1998). To clarify how this finding may be affected by differential cholesterol conditions, we determined the time dependence of L (tether length) and F b for tethers connecting a leukocyte to an endothelial cell (see Materials and Methods).…”
Section: Cholesterol Enrichment Reduces Bond Forcementioning
confidence: 99%
“…where ε is the gap width between the cell and the pipette wall (Shao and Xu, 2002;Shao et al, 1998). Note that this solution is not accurate under our experimental conditions when a cell is positioned close to the pipette tip (Fig.…”
Section: Discussionmentioning
confidence: 93%